2018
DOI: 10.1038/s41467-017-02434-y
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-optic metadevice for all-optical signal modulation based on coherent absorption

Abstract: Recently, coherent control of the optical response of thin films in standing waves has attracted considerable attention, ranging from applications in excitation-selective spectroscopy and nonlinear optics to all-optical image processing. Here, we show that integration of metamaterial and optical fibre technologies allows the use of coherently controlled absorption in a fully fiberized and packaged switching metadevice. With this metadevice, which controls light with light in a nanoscale plasmonic metamaterial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 37 publications
0
75
1
Order By: Relevance
“…Various platforms (e.g., plasmonics [9][10][11][12] , photonic crystals 13,14 , and metasurfaces [15][16][17] , etc.) are now available for forming Ψ gates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various platforms (e.g., plasmonics [9][10][11][12] , photonic crystals 13,14 , and metasurfaces [15][16][17] , etc.) are now available for forming Ψ gates.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been several proposals and some experimental demonstrations of optical logic operations employing linear optical components [7][8][9][10][11][12][13][14][15][16][17] . For example, a simple beam splitter can perform various types of approximate Boolean logic gates as a result of optical interference.…”
mentioning
confidence: 99%
“…We have previously shown that coherent absorption and coherent transparency enable logic NOT, XOR and AND functions at up to 40 Gbit/s [27]. While we are not able to generate faster data signals, our results indicate that our fibre-optic interferometer with its metamaterial absorber could perform these functions at data rates as high as 1 Tbit/s.…”
mentioning
confidence: 58%
“…It has enabled 11 fs dark pulse generation [24], polarization modulation, image processing and various logic functions in free space [25]. Recently, the concept was applied to demonstrate NOT, XOR and AND functions at up to 40 Gbit/s in a fibre-optic interferometer [27].…”
mentioning
confidence: 99%
“…The signal processing opportunities presented by coherent interaction of light with light on 2D matter in a four-port device as discussed above have been investigated in detail in a theoretical study by Fang et al 75 followed by recent experimental demonstrations [76][77][78] . They include transistor-like small-signal amplification as well as logical operations NOT, XOR, XNOR on phase-modulated data and NOT, XOR, AND, OR on intensitymodulated data, promising fast and low energy information processing in novel coherent data processing architectures and locally coherent networks that are becoming part of the mainstream telecommunications agenda.…”
Section: Data and Image Processing With Coherent Metadevicesmentioning
confidence: 99%